Portable Therapeutic Guided Wrist Flexion Exerciser Device for Recovery Monitoring - Jumadi, Nur Anida; Kinatu, Mack Donald Sangkah; Mohd Nasir, Mohammad Fairuz (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Wrist pain and stiffness is a common complaint for many people. This problem is triggered by many factors such as injuries caused by sudden impact, an activity that involves repetitive wrist motions as well as outstretched hand during falling forward. Based on the key rehabilitation engineering principles as well as ergonomics principles, this paper discusses the development of wrist flexion rehabilitation device for recovery monitoring. The user will be guided throughout wristflexion exercise session where the Arduino Mega has been utilized to control the whole operating system. Several sensors have been employed to gather all necessary inputs required for training counting system and determination of bending degree. Furthermore, rapid prototyping technique using 3D technology has been implemented for fabricating wrist flexion assembly parts. Besides that, this device is also equipped with data logging system where the physiotherapist is able to use the stored data for monitoring the recovery process. Data from mock training revealed that the developed device is able to guide the user throughout the rehabilitation process.